PENILAIAN PSIKOMOTOR DAN RESPON SISWA DALAM PEMBELAJARAN SAINS FISIKA MELALUI PENERAPAN PENEMUAN TERBIMBING DI SMP NEGERI 20 PEKANBARU - Zulhelmi Zulhelmi (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2009)
The purpose of this study is, 1). Describe the result of psychomotor learning physics students in learningthrough the application of guided discovery on the power dynamic subject matter. 2). Describe the studentresponse to the application of guided discovery learning subject matter physics, especially in dynamic power.These research is quasi- experiment involving 40 students of class IX7 SMPN 20 Pekanbaru. Implementationstudy done four times the meeting. Data collected through the test show the work (psychomotor tests),questioner from observation. Data analyzed by descriptive. Results of the research shows, 1). Forces theaverage absorbed a lot of students psychomotor 92.03 % with very good category. 2). Students learn theclassical completeness 100 % with complete categories. 3). Terms of learning materials 100 % with completecategories, 4). Student response to the application of guided discovery approach to learning is very goodphysics.